Dietary Pattern and Anemia among Indonesian Female Migrant Workers in Taiwan (Proceedings of the International Conference on Public Health, 2019)
Abstract: Migration has been associated with increased vulnerability to anemia. However, effects of dietary acculturation on anemia among female migrant workers (FMWs) are not clear. The aim of this study was to investigate effects of dietary acculturation on anemia among Indonesia FMWs in Taiwan. In total, 235 Indonesian FMWs aged 20-50 years living in Taipei city were included. The hemoglobin (Hb) levels was measured using single fingerpick by HemoCue. Dietary patterns were identified using principal component (PCA) analysis from 28 food groups. The mean age was 32.51 ± 6.89 years and mean Hb level was 12.77 + 1.50 g/dL (non-anemia: 13.44 + 0.96 g/dL and anemia: 10.80 + 0.93 g/dL; p< 0.001). The prevalence of anemia was 25.53%. Six dietary patterns were obtained by the PCA: coffee; healthy; modern; Indonesian, Taiwanese; meat and dairy. Taiwanese dietary pattern, characterized by high consumption of soy products, mushroom/seaweed, poultry, liver/organs, rice and soft/fizzy drink, protected against anemia: 1.000 (Ref), 0.485 (0.212 – 1.111), 0.360 (0.152 – 0.853), 0.273 (0.108 – 0.691), for quintile (Q) 1 Q1, Q2, Q3, and Q4 respectively (P for trend< 0.003). Our finding suggests that successful dietary acculturation to the host country may provide beneficial effects against anemia among FMWs.
Keywords: Dietary Acculturation; Anemia; Indonesia female migrant workers; Taiwanese diet